2006
DOI: 10.1620/tjem.209.361
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Undifferentiated Carcinoma of the Ascending Colon with Rapid Enlargement after Resection: Report of a Case and Review of the Literature

Abstract: Although adenocarcinoma represents the vast majority of neoplasms of the large intestine, small cell undifferentiated carcinoma (SCUC) also arises from the colorectum. SCUC of the colorectum is highly malignant and shares the similarities in histologic characteristics, behavior, and histochemistry with SCUC of the lung. We report herein a case of SCUC in the ascending colon with rapid enlargement after resection. A 70-year-old male, who presented to a nearby physician with chief complaints of pain in the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…In the above study of 81 patients, the median time to relapse following initial response in patients with limited disease was 11.5 months [9]. Another study of 16 patients with reported rectal SCC had only 3 long-term survivors who were alive 5 years after the time of diagnosis and as expected, all of them had limited disease [10]. …”
Section: Discussionmentioning
confidence: 83%
“…In the above study of 81 patients, the median time to relapse following initial response in patients with limited disease was 11.5 months [9]. Another study of 16 patients with reported rectal SCC had only 3 long-term survivors who were alive 5 years after the time of diagnosis and as expected, all of them had limited disease [10]. …”
Section: Discussionmentioning
confidence: 83%
“…Colorectal extrapulmonary small-cell carcinoma (EPSCC) is rare with a proposed incidence of 0.3% of all colorectal cancer, according to the National Cancer Institute. [5] Yasui et al [6] reported that colorectal EPSCC was located in the cecum in 7 paitnets (18.4%), ascending colon in 7 patients (18.4%), transverse colon in 3 patients (7.9%), sigmoid colon in 3 patients (7.9%), rectum in 16 patients (42.1%), and proctos in 2 patients (5.3%). The majority of patients had SCC in the recutm.…”
Section: Discussionmentioning
confidence: 99%
“…[7,10,11] In colorectal SCC, the mean survival times for patients who underwent resection only and for those who also underwent adjuvant chemotherapy were 67.0 and 121.4 weeks, indicating a longer survival time with adjuvant chemotherapy. [6]…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate of SCCC is much lower than that of all cervical cancers 4 5. The clinicopathological features of SCCC are similar to those of small-cell carcinoma that arise in the lung6 and other extrapulmonary organs, including breast,7 liver,8 salivary gland,9 stomach,10 colon,11 prostate,12 urinary bladder,13 kidney14 and oesophagus 15. Histologically, small-cell carcinoma was characterised by neuroendocrine-like architectural patterns, including nested and trabecular growth with common features 16.…”
Section: Introductionmentioning
confidence: 85%